2018
DOI: 10.1002/jssc.201800171
|View full text |Cite
|
Sign up to set email alerts
|

Development of an analytical strategy to identify and classify the global chemical constituents of Ziziphi Spinosae Semen by using UHPLC with quadrupole time‐of‐flight mass spectrometry combined with multiple data‐processing approaches

Abstract: According to traditional Chinese medical theory, Ziziphi Spinosae Semen needs to be stir-fried before clinical application for its sedative-hypnotic effect enhancement. A rapid and comprehensive analysis strategy of ultra high performance liquid chromatography with quadrupole time-of-flight mass spectrometry and multiple data analysis platforms was developed for the efficient and sensitive identification of components in crude and parched Ziziphi Spinosae Semen to explore the composition changes that happen du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In our future report, we aim to show the multi-ion channel mechanism of DFD. In addition, with the development of mass spectrometry, multiple constituents of the components of DFD have been analyzed and characterized in recent years [29][30][31][32][33][34]. Modern pharmacological studies have shown that the components of DFD have anti-inflammatory [35][36][37][38][39], antioxidative stress [40][41][42], and myocardial protection [42][43][44][45] effects.…”
Section: Discussionmentioning
confidence: 99%
“…In our future report, we aim to show the multi-ion channel mechanism of DFD. In addition, with the development of mass spectrometry, multiple constituents of the components of DFD have been analyzed and characterized in recent years [29][30][31][32][33][34]. Modern pharmacological studies have shown that the components of DFD have anti-inflammatory [35][36][37][38][39], antioxidative stress [40][41][42], and myocardial protection [42][43][44][45] effects.…”
Section: Discussionmentioning
confidence: 99%
“…var. spinosa (Bunge) Hu ex H. F. Chou, is a well‐known traditional Chinese medicine that has been used to treat anxiety and insomnia for thousands of years in China . Modern pharmacological research shows that the extract of ZS possesses many kinds of biological activities including a sedative‐hypnotic effect , an antidepressant effect , an anxiolytic effect , and so on.…”
Section: Introductionmentioning
confidence: 99%
“…var. spinosa (Bunge) Hu ex H. F. Chou, is a wellknown traditional Chinese medicine that has been used to treat anxiety and insomnia for thousands of years in China [1,2]. Modern pharmacological research shows that the extract of ZS possesses many kinds of biological activities including a Article Related Abbreviations: BV, bed volume; prep-HPLC, preparative high-performance liquid chromatography; ZS, Ziziphi Spinosae Semen.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies showed that ZSS is effective in treating insomnia, anxiety, neurasthenic, and depression (Xiao, Wang, Luo, & Lu, ). C‐glycoside flavonoids and saponins are the major constituents of ZSS (Zhang et al, ; Zhang, Zhang, & Xie, ; Zhu et al, ), such as spinosin, 6′′′‐feruloylspinosin, jujuboside A, and jujuboside B. These components exhibited neuroprotective (Liu et al, ; Xu et al, ), sedative, and hypnotic (Wang, Ma, Xie, & Pang, ) effects, and are beneficial for treating cognitive dysfunction (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the chemical profiling of ZSS and pharmacokinetic study of one or two compounds of ZSS using LC–MS. For instance, Zhu and coworkers () identified 40 components from crude and parched ZSS using UPLC‐Q‐TOF/MS. Moreover, Liu and coworkers () studied pharmacokinetic behavior of jujuboside A in rats.…”
Section: Introductionmentioning
confidence: 99%